2014
DOI: 10.1155/2014/125452
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Zinc Levels of Patients with Thalassemia Compared to Their Siblings

Abstract: Zinc (Zn) is essential for appropriate growth and proper immune function, both of which may be impaired in thalassemia children. Factors that can affect serum Zn levels in these patients may be related to their disease or treatment or nutritional causes. We assessed the serum Zn levels of children with thalassemia paired with a sibling. Zn levels were obtained from 30 children in Islamabad, Pakistan. Serum Zn levels and anthropometric data measures were compared among siblings. Thalassemia patients' median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
15
1
Order By: Relevance
“…5 Iron levels of the control and the thalassemia major patient groups (deferoxamine (DFO), deferiprone (DFP) and deferasirox (DFX)). Bars represent mean ± standard deviation a correlation in zinc level between TM patients and their siblings as mentioned before [7]. Others showed no mineral deficiency in TM patients [14,16].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…5 Iron levels of the control and the thalassemia major patient groups (deferoxamine (DFO), deferiprone (DFP) and deferasirox (DFX)). Bars represent mean ± standard deviation a correlation in zinc level between TM patients and their siblings as mentioned before [7]. Others showed no mineral deficiency in TM patients [14,16].…”
Section: Discussionmentioning
confidence: 83%
“…Most of the patients had used zinc when they were giving the blood sample for the current study. A prospective study was performed to determine the zinc level in thalassaemia patients and their siblings [7]. That study revealed that patients' serum Zn values correlated with their siblings', and they suggested that serum Zn levels are possibly more influenced by familial and environmental factors rather than by thalassaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical growth is relatively normal up until 9-10 years of age but the majority of thalassemia patients fail to achieve the same final height as their normal peers [4]. Growth retardation in thalassemia is a well-observed phenomenon with a frequency between 25-66% globally [3,[5][6][7][8] and 20-57% nationally [9][10][11]. Growth retardation is multifactorial and the etiology varies with age.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have compared the serum zinc level in thalassmics and their control population but results are conflicting; serum zinc level were comparable in both the thalassmics and their siblings in Pakistani children (median serum zinc level -1000 vs 920 µ gm/l vs respectively) lower in thalassmics in comparison to control. 14 In Egypt and Iraq (882.8±177.6 vs 1135±153.9 and 386.5±202.5 vs 964.4±276.3 µgm /l respectively) and were higher in thalassemics in comparison to control in Jordan (2208±113 vs 1053±120.1 µ gm/l respectively). 5,15,16 In the present cohort median serum zinc level was found to be 924.85 µ gm/l.…”
Section: Discussionmentioning
confidence: 87%